EXPLORING THE CONTRIBUTION OF FAITH-BASED ORGANISATIONS TO THE RESILIENCE OF MIGRANT FAMILIES IN INDONESIA AND TAIWAN - Gusman, Yuherina; Muhaimin, Ramdhan; Rahman, Riki; Syuan-yuan Chiou (Balai Penelitian dan Pengembangan Agama Jakarta, 2025)
This study examines the role of faith-based organizations (FBOs) as a social infrastructure that supports the resilience of Indonesian migrant families in Indonesia and Taiwan. Data were collected qualitatively from 15 migrant workers, 15 left-behind children, 15 caregivers, 4 FBOs in Indonesia, and 5 FBOs in Taiwan. Data were collected in 2024 and 2025 using semi-structured, in-depth interviews. This study used an interpretivist paradigm to examine how FBOs strengthen the resilience of Indonesian migrant families. The participants were selected with purposive and snowball sampling. The findings show that at the micro level, faith provides emotional endurance and moral guidance for migrant workers but not for their children and caregivers; at the meso level, FBOs such as Dompet Dhuafa, Mandiri Amal Insani, Rumah Edukasi Kenanga, Majelis Taklim Parenting Nabawiyah, and Salimah Taiwan institutionalize care through religious education, parenting training, and psychosocial support. At the macro level, transnational faith networks supplement formal policy frameworks by providing moral and psychosocial protection. The study broadens the concept of social infrastructure to include religious and moral systems as key components of family resilience. It also integrates resilience theory with faith and migration studies and provides empirical evidence that FBOs can help develop more inclusive, culturally grounded transnational social policies.